Evaluation of Materials in a Biomechanical System for Uses in Industrial Lifting Activities - Roberto L. Avitia; Gustavo L. Badilla; Rubén C. Martínez; Jose A. Cárdenas-Haro; Marco A. Reyna; Miguel E. Bravo-Zanoguera (Advances in Materials Science and Engineering)
A biomechanical system is proposed for the emulation of the movement of human arm, leg, and spine movements, as an industry alternative to manage heavy operations in a manufacturing process. The Matlab® programming environment is used as a simulation tool for the analysis and validation of this proposed biomechanism. This machine would reduce the accidents due to human exposure to risky industry environments like the particular one at the host company that we are using as a model for our research. They claim that the accidents in this area alone arise to around thirty percent of the total, causing a decrease in the productivity of the company and other economic losses derived from the worker injuries and insurances.